Anti-Inflammatory Properties of Menthol and Menthone in Schistosoma mansoni Infection - Zaia, Mauricio G.; Cagnazzo, Túlio di Orlando; Feitosa, Karina A.; Soares, Edson G.; Faccioli, Lúcia H.; Allegretti, Silmara M.; Afonso, Ana; Anibal, Fernanda de Freitas (Frontiers in Pharmacology, 2016)
Schistosomiasis is a parasitic disease caused by several species of trematode worms and it is believed that more than 261 million people are affected worldwide. The development of new drugs has become essential due to the risk of the parasite to become resistant to Praziquantel, the only drug available for this infection. This study evaluated parasitological, immunological and histological parameters in Schistosoma mansoni infected mice treated with an herbal commercial medicine. This drug consists of menthol (30-55%) and menthone (14-32%). A 60 day treatment regimen with the herbal medicine decreased the number of S. mansoni eggs in the faeces, liver and intestine and reduced the number of hepatic granulomas. In addition, a reduction of 84% in blood eosinophilia and a decrease in the IL-4 and IL-10 blood levels after treatment, was observed. Therefore, we propose that schistosomiasis treatment with this herbal medicine, consisting of menthol and menthone, for 60 days has an immunomodulatory and anti-inflammatory action in this animal model of schistosomiasis thus contributing to the decrease in physio pathological effects caused by Schistosoma mansoni infection.